2012
DOI: 10.1002/dvdy.23753
|View full text |Cite
|
Sign up to set email alerts
|

Paladin (X99384) is expressed in the vasculature and shifts from endothelial to vascular smooth muscle cells during mouse development

Abstract: Background: Angiogenesis is implicated in many pathological conditions. The role of the proteins involved remains largely unknown, and few vascular‐specific drug targets have been discovered. Previously, in a screen for angiogenesis regulators, we identified Paladin (mouse: X99384, human: KIAA1274), a protein containing predicted S/T/Y phosphatase domains. Results: We present a mouse knockout allele for Paladin with a β‐galactosidase reporter, which in combination with Paladin antibodies demonstrate that Palad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…Paladin expression has also been found in vessels from tumors such as astrocytomas and glioblastomas, as well as in normal human brain vessels. Additionally, paladin has been detected in hematopoietic cells, in agreement with a previous study showing expression of the paladin mRNA in T and B cells . No phenotype has been described so far for Pald1 knockout mice.…”
Section: Class I Cys‐based Phosphatasessupporting
confidence: 90%
See 1 more Smart Citation
“…Paladin expression has also been found in vessels from tumors such as astrocytomas and glioblastomas, as well as in normal human brain vessels. Additionally, paladin has been detected in hematopoietic cells, in agreement with a previous study showing expression of the paladin mRNA in T and B cells . No phenotype has been described so far for Pald1 knockout mice.…”
Section: Class I Cys‐based Phosphatasessupporting
confidence: 90%
“…In this sense, paladin is found in chickens specifically expressed in premigratory and migratory neural crest cells, and is involved in early neural crest migration [80]. Similar data have been found in mouse embryos, where paladin has been detected, in addition to the notochord, in the roof and floor plates of the neural tube, along with rhombomeres 2 and 4, and pharyngeal arches 1 and 2 [81]. Mutation of the two Cys residues present in the phosphatase domains of paladin does not affect its function in chicken neural crest development, indicating the existence of paladin phosphatase-independent functions [80].…”
Section: Paladinsupporting
confidence: 68%
“…Our results also indicate that high-level expression of miR-454-3p might represent a novel diagnostic biomarker for GBM. The other KNG1-regulating ceRNA identified, KIAA1274 (PALD1), is expressed primarily in VECs and vascular smooth muscle cells [30]. Although the expression of KIAA1274 transcripts in the U87 cells used in our experiments was relatively low, a previous study showed that the expression of the PALD1 protein, a putative phosphatase, is restricted to VECs and GBM tumor cells in humans [30].…”
Section: Discussionmentioning
confidence: 65%
“…Of potential controllers of cellular signaling, GAB1 and four Sprouty family members controlling MAPK pathway signaling and Ca 2+ - Calcineurin-NFAT pathway signaling regulators RCAN1 and -2 and TESC were upregulated. Other potential new angiogenesis controlling signaling mediators included PALD1 phosphatase which was recently shown to be expressed in developing vasculature 23 and kinase PBK which was found to phosphorylate p38MAPK in proliferating cells 24 . Interestingly, MARC1 gene encoding an enzyme catalyzing nitric oxide (NO) formation by nitrite reduction 25 was upregulated by both VEGF-A 165 and Vammin.…”
Section: Resultsmentioning
confidence: 99%